REPRESENTASI BRAND ISLAMI DALAM PRODUK KOPI (ANALISIS SEMIOTIKA ROLAND BARTHES PADA BRAND PRODUK KOPI) - Ari Susanti; Nabila Alifiana Firdausi (Universitas Muhammadiyah Jember, 2019)
Brand is the important thing in the process of buying a product. The majority of the Indonesia population is Muslim. Many products in the market are doubtful about the level of halalness. This study examines the representation of Islamic brands of coffee products to influence purchasing decisions. Although many factors influence purchasing decisions such as price and taste, the focus of research remains on Islamic brands. This study is entitled Representation of Islamic Brands in Coffee Products - Roland Barthes's Semiotic Analysis of Coffee Product Brands Sakinah. The Semiotic Roland Barthes approach which is the basis of the analysis of this research is because many cultural elements will be involved. This qualitative research approach with analytical triangulation techniques which are data triangulation, method triangulation and theory triangulation. The results of this study are Islamic brands be easily accepted by the Indonesian market, which is predominantly Muslim. By using Islamic brands that have an impact on consumer confidence in the halalness of the product. In addition, using familiar words such as Sakinah will speed up the process of receiving products in the community. Thus, it will be easily to promoting products in the Indonesia because Islamic brands similar with halal food.